CUTANEOUS MANIFESTATIONS OF ANGIOIMMUNOBLASTIC T-CELL LYMPHOMA - N. G. Chernova (Vestnik Dermatologii i Venerologii, 2018)
Background: Angioimmunoblast T-cell lymphoma (AITL) is a rare T-cell lymphoproliferative disease that is accompanied by generalized lymphadenopathy, hepatosplenomegaly, intoxication symptoms and extranodal lesions. The extranodal manifestations of the disease frequently involve various skin changes. One of the first such manifestations is maculopapular rashes observed in about half of AITL patients and usually preceding the appearance of lymphadenopathy. Other forms of skin lesions accompany the disease considerably less frequently.Aim: To characterize the range of skin changes in patients suffering from AITL, to establish a correspondence between the nature of skin changes and their histological picture.Materials and methods: 54 AITL patients were being treated at the National Research Centre for Hematology from 2000 to 2017, with the male/female ratio being 30/24. The median age was 61 (29–81) years.Results: Changes in the skin were observed in 24 (44.4 %) of 54 AITL patients, out of whom 18 (75 %) and 6 (25 %) were male and female patients, respectively. Maculopapular rash was observed in 22 (91.7 %) out of 24 patients. The morphological and molecular investigations of skin biopsy specimens exhibiting maculopapular rash demonstrated nonspecific reactive changes. Patients with maculopapular rash demonstrated an increase in the level of total (polyclonal) IgE. Specific skin lesions detected in 8 (14.8 %) cases were represented by a ‘livedo reticularis’, focal skin hyperpigmentation, erythroderma, left eyelid tumour and tumour in 3, 2, 1, 1 and 1 cases, respectively.Conclusion: Maculopapular rash frequently observed in AITL patients is a reactive process not associated with a specific skin lesion. Specific skin lesions in AITL are much less common and can be represented by various forms. In some AITL cases, skin changes of the reactive and tumour nature can be simultaneously observed.